2017
DOI: 10.1590/1807-3107bor-2017.vol31.0102
|View full text |Cite
|
Sign up to set email alerts
|

Oral health assessment for users of marijuana and cocaine/crack substances

Abstract: The objective of this study was to assess the oral health status of users of illicit drugs such as marijuana and cocaine/crack and compare it with individuals not using these chemical substances.Questionnaires were applied to 35 illicit drugs users to gather information on demographic status, general health, and use of drugs. Then, a clinical assessment of the oral health condition was performed to collect data on decayed, missing and filled teeth (DMFT) index, salivary flow rate (SFR), and mucosal lesions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 25 publications
0
26
0
8
Order By: Relevance
“…Moreover, the results of authors Mateos Moreno et al (1) coincide with those found in the study by Gigena et al (13), demonstrating a prevalence of rampant caries in users of cannabis and other drugs, with 23.9% of radicular affectation, a higher DMFT value in the group substance abusers with respect to the control group that did not use any psychotropic substances. The study of Sordi et al (14) gave different results on the DMFT index. As analyzed by these authors, the index was lower in the group of cannabis and cocaine users than in the control group of individuals without any drug addiction, the prevalence of caries and missing teeth was higher in the group of cannabis and cocaine users but the number of filled teeth was higher in the control group.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Moreover, the results of authors Mateos Moreno et al (1) coincide with those found in the study by Gigena et al (13), demonstrating a prevalence of rampant caries in users of cannabis and other drugs, with 23.9% of radicular affectation, a higher DMFT value in the group substance abusers with respect to the control group that did not use any psychotropic substances. The study of Sordi et al (14) gave different results on the DMFT index. As analyzed by these authors, the index was lower in the group of cannabis and cocaine users than in the control group of individuals without any drug addiction, the prevalence of caries and missing teeth was higher in the group of cannabis and cocaine users but the number of filled teeth was higher in the control group.…”
Section: Discussionmentioning
confidence: 98%
“…As analyzed by these authors, the index was lower in the group of cannabis and cocaine users than in the control group of individuals without any drug addiction, the prevalence of caries and missing teeth was higher in the group of cannabis and cocaine users but the number of filled teeth was higher in the control group. this could be a consequence of higher access to dental treatment by the control group (14). They also observed a higher prevalence of lesions in the oral mucosa in individuals who used cannabis: stomatitis, candidiasis, keratosis by friction, loss of the papillae of the tongue and obvious signs of poor post-exodontia healing (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…O uso de drogas ilícitas como o crack também acarreta em uma maior prevalência de lesóes na mucosa oral, uma menor taxa de fluxo salivar, além de uma maior experiência de cárie e elevado número de dentes perdidos 12,13 .…”
Section: Introductionunclassified